Colored Water, Trimmed Coffee, and Solid Soup: Etymology of “Edible Traps” in Spanish in Context of Communicative Difficulties - N. F. Mikheeva; E. A. Popova (Научный диалог)
This article explores sources of communicative difficulties such as inter-variant polysemy and inter-variant homonymy, focusing on lexemes from the Spanish thesaurus FOOD that denote liquid food products. The relevance of this study is grounded in the necessity for a comprehensive analysis of alimentary semantics within the national variants of the Spanish language in the context of cultural dialogue. The novelty of the research lies in identifying challenges in intercultural communication through semantic, etymological, and linguocultural analyses of the meanings of the examined lexemes and their stable combinations across different Spanish-speaking countries. Particular attention is given to the influence of extralinguistic factors on communicative difficulties within a multi-national language. The findings suggest that the development of semantics for inter-variant homonyms primarily depends on historical factors, and understanding the differences in meanings of core components within semantic fields related to food in various national variants of Spanish can help alleviate communicative barriers and prevent misunderstandings. Future research perspectives include pragmasemantic structuring of the inter-variant alimentary thesaurus in the target language and applying the results to language teaching.